REVIEW OF THE BOOK “AFRICAN HERBAL PHARMACOPOEIA” BY BRENDLER, T., ELOFF, J. N., GURIB-FAKIM, A., PHILLIPS, L. D. Published by the Association for African Medicinal Plants Standards (2010) - Elujoba, Anthony A (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
I would like to open this brief review by welcoming the pharmacopoeial publication into the league of earlier texts of similar nature in the field of African medicinal plant documentation. The usefulness of a herbal pharmacopoeia in a resource-limiting continent like Africa, cannot be over-emphasised. Firtsly, it would facilitate and fast-track the long awaited and most needed official recognition of African traditional medicine in the region, the evolution of herbal industry in the AFRO region, improved health care delivery among the people as well as bringing about job and wealth creation, through poverty alleviation. Furthermore, it would provide the necessary quality control and monitoring templates for the national or sub-regional Food and Drugs Administration and other relevant drug regulatory/registration authorities on safety of herbal medicines, submitted to them for human and animal health.